Cultivating patient-centered care competence through a telemedicine-based course: An explorative study of undergraduate medical students’ self-reflective writing - Findyartini, Ardi; Hanum, Chaina; Kusumoningrum, Dewi Anggraeni; Putera, Azis Muhammad; Werdhani, Retno Asti; Safitry, Oktavinda; Muktiarti, Dina; Soemarko, Dewi Sumaryani; Wisnu, Wismandari (Frontiers in Public Health, 2023)
Background The COVID-19 pandemic has encouraged adaptations of learning methods in clinical clerkship. There have been limited reports on the merits of involving medical students in telemedicine. This study, therefore, aims to investigate students’ reflection on what they learned and identify the challenges and benefits of doctor-patient interaction through their experience in a telemedicine-based course. Methods A 4-week telemedicine-based course for medical students to participate in telemonitoring of COVID-19 patients undergoing self-isolation was conducted. This is a qualitative study using an interpretive phenomenology design to investigate students’ self-reflection on their experiences in monitoring COVID-19 patients. Students were asked to reflect on their experience upon completion of the course through 750 – 1000 words essays. A thematic analysis which considers units of meaning based on students’ experiences was completed. Results Our study identified four main themes gathered from students’ experiences related to the in the telemedicine-based course: communication and education, professionalism and professional identity formation, system-based practice, and patient-centered care. Conclusion The course was part of an integrative effort involving multiple parties to tackle the burden on the nation’s healthcare system during the pandemic. Telemedicine is part of future medical practice which supports the medical curriculum adaptability along with attempts to develop future-proof medical doctors through various clinical learning experiences.